Creating Markets Out of Nothing: The Case of the Continuing Education System in Greece - YIORGOS, Ioannidis (Journal of Research in Educational Sciences; Vol 7 No 8 (2015): Journal of Research in Educational Sciences, 2015)
The development of the vocational training policy constitutes one of the most interesting examples of a policy which was introduced entirely due to the pressure exercised by the E.U., but it was implemented in such a way that it served the domestic political economy. The seven laws and the dozens of ministerial decrees issued from 1989-2004 reflect the effort made by the state to foster but also control the development of the market, the conflict of interests among the main players–namely those of the state, the private training centers and the social partners– but also the tensions generated by the pressures of the E.U. It will be argued that the development of the continuing education market in Greece can be described and analysed on the basis of three distinct time periods: (a) The period of initial capital accumulation (1989-1994), (b) the period of the controlled clearing of the market (1994-2004) and, (c) the period of the liberalization of the market (2005 - ). In every stage the interests of the main actors were accommodated accordingly, but this was achieved at the expense of the continuing training system’s efficiency. The aim of the paper is to critically assess these developments by focusing on the latent rationality underlying the state’s regulatory actions, as well as on the political economy which these actions have engendered.